Design of Educational Game Tools Recognizing Body Members Using The Kansei Engineering Method - Nugraha Ramadhani; Ismu Kusumanto; Nofirza Nofirza (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Education is very important in realizing a strong and advanced nation. So, the process must be carried out early. Therefore, Early Childhood Education is the main foundation for the development of a nation's generation. While the standards of Early Childhood Education are not evenly distributed, in fact, there are still many that are lacking, especially in the learning media of Educational Game Tools/Alat Pembelajaran Edukatif (APE). In this research, an Educational Learning Tool will be made in the form of a puzzle using the Kansei words and Kensei engineering methods. The results of this study indicate that the child's response is very good and very helpful in the learning process. The combination of the Kansei words and Kansei engineering methods produces a unique educational game tool that makes children more interested in participating in learning